Oral cancer immunology: state of the art and future perspectives - Fábio Muradás GIRARDI; Lauren Frenzel SCHUCH; Manoela Domingues MARTINS (Brazilian Oral Research, 2024)
Abstract Oral cancer is a multifactorial disease involving genetic, epigenetic, and environmental factors. The literature indicates that inflammatory cells at the advancing front of the tumor induce a host immune response, preventing the spread of the tumor. However, cancer cells adopt various continued strategies to circumvent this immune surveillance. The complexity of immune mechanisms suggests that there must be virtually individual patterns of anti-tumor immune responses. Due to this important interaction of cancer with the immune system, the objective of the present study was to provide an up-to-date overview of immuno-oncology focused on oral cancer, summarizing the basic immunology, the classic risk factors, immunotherapy, and future treatment and prognostic perspectives.